Digital Evaluation Media in Elementary Schools – Literatur Review - Persada, Yuris Indria; Oktarianto, M. Luthfi; Maharani SW, Aqina Hawa; Yunita, Annisa Rahmah; Vinardi, Aurel Sheva; Mahandi, Ata; Fitriandari, Dini Wiranti (Universitas Negeri Malang, 2024)
This literature review explores the integration of digital evaluation media in elementary schools, highlighting its potential to enhance student engagement, personalize learning, and support data-driven decision-making. The reviewed studies indicate that digital tools, such as formative assessments, digital portfolios, and educational games, provide timely feedback and foster self-regulated learning. However, challenges related to the reliability and validity of digital assessments, as well as the need for teacher training, are identified. The analysis emphasizes the importance of professional development for educators to effectively use digital tools and interpret assessment data. Additionally, the role of data analytics in informing instructional decisions and addressing individual learning needs is discussed. The findings suggest implications for educational practice and policy, including the establishment of guidelines for digital assessment standards and efforts to bridge the digital divide. While digital evaluation media presents promising opportunities, successful implementation requires addressing technical, pedagogical, and equity-related challenges. The review concludes that a collaborative approach involving educators, researchers, and policymakers is essential for maximizing the impact of digital assessment in elementary education.